Chronic Hepatitis B Virus Infection in Four (4) Asymptomatic Prospective Employees: A Short Correspondence - Tetteh, Ato Kwamena; Baffe, Charles; Bram, Prince; Arthur, Sadick; Aglago, Godsway; Agyarko, Edward (Journal of Diseases, 2020)
Aim: This study aimed at compiling all hepatitis B results for prospective employees screened at the Cape Coast Metropolitan Hospital. This information is relevant in identifying those who are already infected, as well as susceptible individuals, to promote the establishment of prevention and control measures within work environments. Method: This study extracted data from laboratory records into Microsoft Excel and used for the analysis. Results: In this report, 13.3% (4/30) of prospective employees were found to be sero-positive for hepatitis B surface antigen (HBsAg). The remaining were sero-negative (susceptible), and required vaccination. All of the four (4) found to be sero-positive were chronically infected [both hepatitis B envelope antibody (HBeAb) and core antibody (HBcAb) - positive], that is, capable of transmitting to susceptible individuals if the proper infection prevention practices are not well implemented in their homes and work places. Only males were found to be positive, while all females were negative. Conclusion: Continuous education, screening, management of infected individuals and vaccination of the susceptible, will go a long way to curbing the spread of hepatitis B infection.